Using a decision support system tool for healthcare technology assessments. - Sloane, E.B (IEEE Engineering in medicine and biology magazine)
This article discusses a healthcare technology assessment application using a well-developed business tool from the operations research/operations management (OR/OM) field, the analytic hierarchy process (AHP). The AHP methodology provides a proven, structured, and well-documented tool for conducting HTAs for hospitals, integrated delivery networks, or other healthcare providers. A case study based on the selection of a neonatal ventilator is used to illustrate a successful use of the AHP for HTA. Clinical engineers can use this design as a prototype for performing HTAs in their own institutions.